Illustrated State‐of‐the‐Art Capsules of the ISTH 2020 Congress. Issue 5 (12th July 2020) - Ariens, Robert; Becattini, Cecilia; Bender, Markus; Bergmeier, Wolfgang; Castoldi, Elisabetta; Devreese, Katrien; Ellis, Martin; Gailani, David; Ignjatovic, Vera; James, Paula D.; Kerrigan, Steven; Lambert, Michele; et al.
Abstract: The 2020 Congress of the International Society of Thrombosis and Haemostasis (ISTH) was held virtually July 12‐15, 2019, due to the coronavirus disease 2019 pandemic. The congress convenes annually to discuss clinical and basic topics in hemostasis and thrombosis. Each year, the program includes State of Art (SOA) lectures given by prominent scientists. Presenters are asked to create Illustrated Capsules of their talks, which are concise illustrations with minimal explanatory text. Capsules cover major themes of the presentation, and these undergo formal peer review for inclusion in this article. Owing to the shift to a virtual congress this year, organizers reduced the program size. There were 39 SOA lectures virtually presented, and 29 capsules (9 from talks omitted from the virtual congress) were both submitted and successful in peer review, and are included in this article. Topics include the roles of the hemostatic system in inflammation, infection, immunity, and cancer, platelet function and signaling, platelet function disorders, megakaryocyte biology, hemophilia including gene therapy, phenotype tests in hemostasis, von Willebrand factor, anticoagulant factor V, computational driven discovery, endothelium, clinical and basic aspects of thrombotic microangiopathies, fibrinolysis and thrombolysis, antithrombotics in pediatrics, direct oral anticoagulant management, and thrombosis and hemostasis in pregnancy. Capsule authors invite virtual congress attendees to refer to these capsules during the live presentations and participate on Twitter in discussion. Research and Practice in Haemostasis and Thrombosis will release 2 tweets from @RPTHJournal during each presentation, using #IllustratedReview, #CoagCapsule and #ISTH2020. Readers are also welcome to utilize capsules for teaching and ongoing education.